Identification of Francisella novicida mutants that fail to induce prostaglandin E2 synthesis by infected macrophages - Woolard, Matthew D.; Barrigan, Lydia M.; Fuller, James R.; Buntzman, Adam S.; Bryan, Joshua; Manoil, Colin; Kawula, Tom; Frelinger, Jeffrey A. (Frontiers in Microbiology, 2013)
Francisella tularensis is the causative agent of tularemia. We have previously shown that infection with F. tularensis Live Vaccine Strain (LVS) induces macrophages to synthesize prostaglandin E2 (PGE2). Synthesis of PGE2 by F. tularensis infected macrophages results in decreased T cell proliferation in vitro and increased bacterial survival in vivo. Although we understand some of the biological consequences of F. tularensis induced PGE2 synthesis by macrophages, we do not understand the cellular pathways (neither host nor bacterial) that result in up-regulation of the PGE2 biosynthetic pathway in F. tularensis infected macrophages. We took a genetic approach to begin to understand the molecular mechanisms of bacterial induction of PGE2 synthesis from infected macrophages. To identify F. tularensis genes necessary for the induction of PGE2 in primary macrophages, we infected cells with individual mutants from the closely related strain F. tularensis subspecies novicida U112 (U112) two allele mutant library. Twenty genes were identified that when disrupted resulted in U112 mutant strains unable to induce the synthesis of PGE2 by infected macrophages. Fourteen of the genes identified are located within the Francisella pathogenicity island (FPI). Genes in the FPI are required for F. tularensis to escape from the phagosome and replicate in the cytosol, which might account for the failure of U112 with transposon insertions within the FPI to induce PGE2. This implies that U112 mutant strains that do not grow intracellularly would also not induce PGE2. We found that U112 clpB::Tn grows within macrophages yet fails to induce PGE2, while U112 pdpA::Tn does not grow yet does induce PGE2. We also found that U112 iglC::Tn neither grows nor induces PGE2. These findings indicate that there is dissociation between intracellular growth and the ability of F. tularensis to induce PGE2 synthesis. These mutants provide a critical entrée into the pathways used in the host for PGE2 induction.